(untitled) (CAHIERS MAGELLANES-NS, 2024)
A binary metal oxide Al2O3-ZrO2 (1:1) material catalyzed efficiently the solventless oxidation of benzyl alcohol (BOL) by tert-butyl hydrogen peroxide (TBHP) and produced selectively the benzaldehyde (BAL) in high yields. The mixed oxide of Al2O3-ZrO2 (1:1) catalyst was prepared via an ultra-diluted co-precipitation method and characterized by XRD, N2 adsorption-desorption, NH3-TPD and CO2-TPD, SEM and XPS techniques. The Al2O3-ZrO2 (1:1) mixed oxide catalyst showed a higher conversion (71%) of benzyl alcohol and selectivity towards the benzaldehyde (85%) product in comparison to that of individual metal oxide catalysts i.e. Al2O3 and ZrO2. The influence of reaction parameters like temperature, reaction time and catalyst loading were studied to optimize the catalytic conditions. Catalyst recovery and reusability experiments revealed that the above binary metal oxide is stable up to five catalytic cycles. The optimized catalytic oxidation conditions were extended to study the substrate scope and a total of eight different BAL products were efficiency synthesized.